Effect of road surface equality on the driver's functional state - Sotnikova, Anna (Lviv Polytechnic Publishing House, 2016)
The driver is a key element in the system of interaction "driver - vehicle - road - environment". About 70 - 90% of all failures falls on errors of this subsystem. One of the main indicators that reflect the willingness of the driver to the professional activity is its functional state. The aim of this work is to identify the dependence of values of the driver's functional state of road surface equality. Therefore were analyzed the methods and means of assessing the quality of the roadway, determined the characteristics of the functional state of the driver, and conducted field researches and desk studies for determination of driver's index of activity of regulatory systems in different driving conditions (satisfactory and poor road surfaces).
Keywords: road surface equality; driving conditions; functional state; index of activity of regulatory systems; electrocardiogram